Kajian Kandungan Fe dalam Air Tanah Terhadap Kadar Ekskresi Yodium dalam Urin pada Anak Sekolah di Desa Cerme Kecamatan Panjatan Kabupaten Kulon Progo - Vivi Linda Fristianti; Nur Hidayat; Slamet Iskandar (JURNAL NUTRISIA, 2017)
Background : IDD problem is a serious problem, 33% of districts in Indonesia are endemic, 21% of endemic mild, moderate endemic 5% and 7% by weight endemic. Urine Iodine Excretion (EYU) illustrates the iodine intake of a person, because 90% of the iodine that enter the body are excreted through the urine. Blocking agents are substances certain minerals such as iron, manganese and calcium, which can bind iodine in groundwater. Objectives : This study aims to determine the relationship of Fe content in ground water sources against EYU levels in school children in the village of the District Cerme Panjatan Kulon Progo. Methods : An observational analytic research with cross sectional design. Data collection is done in May - June 2015. Location research Elementary School Cerme, District Panjatan Kulon Progo. The subjects of the study as many as 34 children in elementary school classroom Cerme 3, 4 and 5 were taken by simple random sampling. Well water and urine samples taken students then tested the iron in the Central Health Laboratory test Yogyakarta and iodine in urine in Magelang BP2GAKY Laboratory. Data analysis using Spearman Range test with significancy level : 0.05. Result : Fe content in the ground water is below the normal threshold is <0.3 mg / L. While levels EYU school children who are under the optimal level of 5.9%, the optimal level of 32.4%, and the optimum levels above 61.8% (optimal: 100 - 199μg / L). Conclusion : There was no significant relationship between the Fe content in groundwater with levels of EYU in school children in District Panjatan Kulon Progo (p = 0.447). Keywords: Fe, EYU